Retrospective Analysis of Factors Associated with Long-Stay Hospitalizations in an Acute Psychiatric Ward - Di Lorenzo R; Montardi G; Panza L; Del Giovane C; Saraceni S; Rovesti S; Ferri P (Dove Medical Press, 2020)
Rosaria Di Lorenzo,1 Giulia Montardi,2 Leda Panza,3 Cinzia Del Giovane,4 Serena Saraceni,2 Sergio Rovesti,5 Paola Ferri6 1Psychiatric Intensive Treatment Facility, Department of Mental Health and Drug Abuse, Az-USL Modena, Modena 41122, Italy; 2School of Specialization in Psychiatry, University of Modena and Reggio Emilia, Modena 41124, Italy; 3School of Nursing, University of Modena and Reggio Emilia, Modena 41124, Italy; 4Head of Statistics and Methodology, Institute of Primary Health Care (BIHAM), Bern, Switzerland; 5General and Applied Hygiene, Department of Biomedical, Metabolic and Neural Sciences, Modena 41125, Italy; 6Nursing, Department of Biomedical, Metabolic and Neural Sciences, Modena 41125, ItalyCorrespondence: Rosaria Di LorenzoPsychiatrist, Psychiatric Intensive Treatment Facility, Az-USL Modena, Modena 41122, ItalyEmail r.dilorenzo@ausl.mo.itPurpose: To evaluate the longest hospitalizations in an acute psychiatric ward [Service of Psychiatric Diagnosis and Treatment (SPDT)] and the related demographic, clinical and organizational variables to understand the factors that contribute to long-stay (LOS) phenomenon. The term “long stay” indicates clinical, social and organizational problems responsible for delayed discharges. In psychiatry, clinical severity, social dysfunction and/or health-care system organization appear relevant factors in prolonging stays.Patients and Methods: We divided all the SPDT hospitalizations from 1 January 2010 to 31 December 2015 into two groups based on the 97.5th percentile of duration: ≤ 36 day (n=3254) and > 36 day (n=81) stays, in order to compare the two groups for the selected variables. Comparisons were made using Pearson’s chi-square for categorical data and t-test for continuous variables, the correlation between the LOS, as a dependent variable, and the selected variables was analyzed in stepwise multiple linear regression and in multiple logistic regression models.Results: The longest hospitalizations were significantly related to the diagnosis of “schizophrenia and other psychosis” (Pearson Chi2=17.24; p=0.045), the presence of moderate and severe aggressiveness (Pearson chi2=29; p=0.000), compulsory treatment (Pearson Chi2=8.05; p=0.005), parenteral or other route administration of psycho-pharmacotherapy (Pearson Chi2=12.91; p=0.007), poli-therapy (Pearson Chi2=6.40; p=0.041), complex psychiatric activities (Pearson Chi2=12.26; p=0.002) and rehabilitative programs (Pearson Chi2=37.05; p=0.000) during the hospitalization and at discharge (Pearson Chi2=29.89; p=0.000). Many demographic and clinical variables were statistically significantly correlated to the LOS at our multiple linear and logistic regression model.Conclusion: In our sample, clinical illness severity and need for complex therapeutic and rehabilitative treatments were associated with prolonged psychiatric hospitalizations. Understanding this phenomenon can have not only economic but also clinical, ethical and social relevance.Keywords: psychiatric long-stay, acute psychiatric ward, predictors of long-stay, illness severity